Flow in thermosiphon regimen in an all glass vacuum tube solar collector // Flujo en un colector de tubos al vacío en régimen termosifón - Cisneros Ramírez, César A.; Recalde Moreno, Celso (Ingeniería Mecánica. Revista electrónica. ISSN 1815-5944, 2021)
Abstract Due to the heating of the fluid, it decrease its density and thus becomes lighter. That is why a flow of hot fluid appears that rises through the tube towards the storage tank. At the same moment the cold fluid descends and thus a natural circulation of the fluid is established. In this work, a relationship is obtained to determine the flow based on the different variables involved in the process. From this, the influence of the angle of inclination and the length diameter relationship of the tube is obtained. Key words: collector, thermosiphon, solar energy